Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1099/vir.0.012724-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of the T112 PrP variant in sheep challenged with bovine spongiform encephalopathy

Abstract: Sheep with an ARQ/ARQ PRNP genotype at codon positions 136/154/171 are highly susceptible to experimental infection with bovine spongiform encephalopathy (BSE). However, a number of sheep challenged orally or intracerebrally with BSE were clinically asymptomatic and found to survive or were diagnosed as BSE-negative when culled. Sequencing of the full PRNP gene open reading frame of BSE-susceptible and -resistant sheep indicated that, in the majority of Suffolk sheep, resistance was associated with an M112T PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 54 publications
(47 reference statements)
3
24
2
Order By: Relevance
“…The BSE incubation period did not alter with the doses used, but there was an association of codon 141 with the length of the incubation period in that animals of the ARQ/ARQ genotype had the shortest incubation periods if they were also LL 141 , longer if FF 141 , and longer still if LF 141 . New Zealand Cheviot sheep have a polymorphism at codon 168 that has been associated with BSE resistance (22), and codon 112 has been shown in other sheep also to be associated with differences in BSE (47). However, in the sheep in the present study, codons 168 and 112 did not vary, except in one single animal that was PL 168 , and no additional codon variants were found.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The BSE incubation period did not alter with the doses used, but there was an association of codon 141 with the length of the incubation period in that animals of the ARQ/ARQ genotype had the shortest incubation periods if they were also LL 141 , longer if FF 141 , and longer still if LF 141 . New Zealand Cheviot sheep have a polymorphism at codon 168 that has been associated with BSE resistance (22), and codon 112 has been shown in other sheep also to be associated with differences in BSE (47). However, in the sheep in the present study, codons 168 and 112 did not vary, except in one single animal that was PL 168 , and no additional codon variants were found.…”
Section: Discussioncontrasting
confidence: 51%
“…In our previous studies we used a dose of 5 g of cattle BSE brain per (adult) sheep and this resulted in clinical disease at an average incubation period of around 800 days (16). The 5-g dose, or even larger amounts, has become the normal oral dose when clinical disease is required for pathogenesis studies in our own and other labs (3,47,52,59). In the present study, the lower doses (ranging from 0.1 g to 1 g per animal) were chosen such that the sheep in the adult group would not all become clinically affected by BSE.…”
Section: Discussionmentioning
confidence: 99%
“…In ARQ/ARQ sheep other additional dimorphisms, which are thought to reduce the risk of having scrapie and/or BSE, namely M112T (Laegreid et al, 2008;Saunders et al, 2009), P168L (Goldmann et al, 2006), M137T (Vaccari et al,. 2009;Maestrale et al, 2009) and I142K (Vaccari et al, 2007), may also give resistance to PrP Sc deposition in the placenta.…”
Section: Several Descriptive Data Suggest That Prpmentioning
confidence: 99%
“…It was recently demonstrated that amino acid substitutions at some of these polymorphisms are associated with resistance to scrapie and bovine spongiform encephalopathy (BSE) in ARQ/ARQ sheep (Vaccari et al, 2007(Vaccari et al, , 2009Laegreid et al, 2008;Maestrale et al, 2009;Saunders et al, 2009). Consequently, it is of interest whether they are also related to PrP Sc deposition in the placenta of scrapie-infected ewes.…”
mentioning
confidence: 99%
“…Other variants also influence susceptibility, for example, H 154 (where H is histidine) (13,(24)(25)(26)(27)(28)(29)(30). Together, this evidence has led to policies for eradication of scrapie in sheep breeds by focusing on codons 136, 154, and 171, in which the different alleles are designated, in respective order, ARQ (the wild type), VRQ, AHQ, and ARR (31,32).…”
mentioning
confidence: 99%